Bio-potential of compost tea from agro-waste to suppress Choanephora cucurbitarum L. the causal pathogen of wet rot of okra - Siddiqui, Yasmeen; Meon, Sariah; Ismail, Mohd Razi; Rahmani, Mawardi (2009)
In vitro and in vivo experiments were carried out to determine the mechanisms involved in suppression of Choanephora cucurbitarum the causal pathogen of wet rot disease of okra by using the tea produced from agro-waste such as rice straw (RST) and empty fruit bunch (EFB) of oil palm composts. Non-sterilized, filter-sterilized and heat-sterilized compost teas were tested on the growth of C. cucurbitarum. The highest percentage of inhibition in conidial germination was obtained by both the non-sterilized RST and EFB compost tea with values of 84% and 79%, respectively. The inhibitory efficacy was reduced significantly (P ≤ 0.05) when the teas were subjected to millipore membrane filters or heat-sterilization. The mycelial growth of C. cucurbitarum was reduced by 100% in plates amended with both the non-sterilized compost tea. Light microscopy micrographs of mycelial samples of C. cucurbitarum exposed to non-sterilized RST and EFB compost tea showed alterations in mycelial morphology and lysis, resulting in inhibition in mycelial growth. Glass house trials indicated that induced host resistance was stimulated in okra plants treated with non-sterilized and filter-sterilized compost teas based on the detection of inducible resistance-related compounds. The mean values for inducible enzymes which have a role in disease resistance [peroxidase (PO), polyphenol oxidase (PPO) and phenylalanine ammonia lyase (PAL)] increased until day 8, which were significantly higher in okra plants pre-treated with non-sterilized tea in view of the high nutritive and microbiological properties. There was a further increase in inducible compounds when the pre-treated okra plants were challenged with C. cucurbitarum. Following the increase in total PO, PPO and PAL activities, development of Choanephora wet rot was delayed, confirming the possible involvement of induced resistance. However, resistance was not maintained since it decreased over time. This could be due to the highly stressed environment of the leaf surfaces which had a detrimental effect on the survival of the antagonists and subsequently affected the efficacy of compost tea. It was therefore suggested that plants should be sprayed at short intervals with the compost tea to sustain the suppressive effect.